Slippery Bottom Boundary Layers: The Loss of Energy From the General Circulation by Bottom Drag. Issue 19 (1st October 2021) - Ruan, Xiaozhou; Wenegrat, Jacob O.; Gula, Jonathan
Abstract: Bottom drag is believed to be one of the key mechanisms that remove kinetic energy from the ocean's general circulation. However, large uncertainty still remains in global estimates of bottom drag dissipation. One significant source of uncertainty comes from the velocity structures near the bottom where the combination of sloping topography and stratification can reduce the mean flow magnitude, and thus the bottom drag dissipation. Using high‐resolution numerical simulations, we demonstrate that previous estimates of bottom drag dissipation are biased high because they neglect velocity shear in the bottom boundary layer. The estimated bottom drag dissipation associated with geostrophic flows over the continental slopes is at least 56% smaller compared with prior estimates made using total velocities outside the near‐bottom layer. The diagnostics suggest the necessity of resolving the bottom boundary layer structures in coarse‐resolution ocean models and observations in order to close the global kinetic energy budget. Plain Language Summary: When an oceanic flow is close to the seafloor, the bottom drag converts its kinetic energy (KE) to heat through viscous friction, and this dissipation of KE has been shown to be very sensitive to the magnitude of the flow. Despite previous estimates indicating the bottom drag being a significant mechanism for removing KE from the ocean's general circulation, large uncertainty still remains. Using high‐resolution numerical simulations of the Atlantic Ocean, we demonstrate that accounting for the velocity reduction through the oceanic bottom boundary layer reduces KE loss from the balanced flow (in which the pressure gradient force and Coriolis force balance) by at least 56% over the continental slopes. This velocity reduction is due to the presence of sloping topography and ocean stratification near the bottom, which should be resolved in future observational and modeling efforts toward a more complete picture of the ocean's energy budget. Key Points: Thermal wind shear in the bottom boundary layer reduces the magnitude of the near‐bottom flow and bottom stress Accounting for boundary layer shear reduces kinetic energy loss from the geostrophically balanced flow by more than 50% Observations and models that do not resolve the bottom boundary layer will overestimate the energy dissipation due to bottom drag